SIPANDAI : PROGRAM EDUKASI TANGGAP GEMPA BAGI PESERTA DIDIK SEKOLAH DASAR MELALUI SOSIALISASI MAHASISWA PEDULI BENCANA DAN LINGKUNGAN - Yuliani, Rostika (Midang, 2026)
Indonesia is a country prone to natural disasters, particularly earthquakes, which can cause loss of life. Improving elementary school students' knowledge is a crucial step in promoting the importance of disaster mitigation literacy, pre-disaster, disaster-related, and safe emergency evacuation procedures at school. Disaster mitigation literacy activities were conducted using animated videos, games, and live simulations at Rancakasumba Private Elementary School. The goal of this activity was to improve elementary school students' disaster mitigation literacy regarding disaster preparedness bags, earthquake awareness, and evacuation routes at school. This activity involved 23 Al-Ghifari University students as facilitators and 28 fourth-grade students from Rancakasumba Private Elementary School. The methods used were game-based learning, animated videos, and live simulations of earthquakes. The study found a significant increase in student knowledge, indicating that games, animated videos, and live simulations can improve disaster mitigation literacy skills. The conclusion from this activity is that ongoing earthquake mitigation literacy socialization activities are necessary to build a culture of disaster awareness.